Perancangan Prototype Aplikasi Olahraga FitenRun Menggunakan Metode User Centered Design - Putri, Dea Amelia; Nabarian, Tifanny (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
Sport is a simple way to improve physical fitness. However, there are several problems with these activities, such as a busy schedule of activities, confusion when starting to exercise due to a lack of information, and queues for using places or tools that interfere with comfort. The UI/UX design of a sports application called FitenRun employs User-Centered Design (UCD). In the UCD stage, there are four key processes: understanding the user's context, specifying user requirements, designing solutions, and evaluating them against those requirements. The application testing stage uses the System Usability Scale (SUS) and Single Ease Question (SEQ) methods. The results of the application design were identified based on user needs through the distribution of questionnaires, with 57 respondents participating. The features produced in the FitenRun application, namely FitRent, are presented as the main feature, with additional supporting features such as FitEvent, FitTrainer, FitChallenge, FitModule, and FitClass. The results of the tests carried out yielded an average score of 85, obtained using six-user testing for SUS, and the average SEQ score was 6.2. Indicating that the system falls into the excellent category, which suggests that the system is suitable for users and shows that potential users can interact easily with the application.